TORTURA INSTITUCIONAL VIA PODER JUDICIÁRIO: quando a busca pela justiça é convertida em tortura às mulheres vítimas de violência doméstica e/ou familiar no Brasil. - OLIMPIO, Werderson Mário Cavalcante (2021)
The Judiciary still needs many advances in the fight and prevention both in relation to the crime of torture and domestic or family violence against women, since They still persist in Brazil, whether in the public or private sphere. In this context, the presente research aims to analyze a configuration of institutional torture by the brazilian Judiciary to women who suffered domestic and or family violence, such as that resulting from the invisibility of domestic and or family violence as a crime of torture linked to there victimization of women who seek the Justice System, from the performance of the 1st Specialized Court of Domestic and Familiar Violence Against Women (1st VEVDFCM) of the District of São Luís/MA and the Court of Justice of the State of Maranhão (TJ/MA). To achieve this goal, the inductive method, a quantitative-qualitative approach, a bibliographic Search, as well as a documentar serch of the judgments of TJ/MA on the crime of torture in the time span from 2016 to 2020, interpreted by thematic contente analysis, were used. In addition, qualitatively, focusing on possible institucional violences, all dissertations from the Postgraduate Program in Law and Justice System Institutions (PPGDIR/UFMA) that had as object the gender violence and field of study a 1st VEVDFCM andor TJ/MA. As a result, the presente work proved the existence of institutional torture through the Judiciary to women suffering from domestic or family violence, materialized in the invisibility of domestic and/or family violence as a crime of torture and in the institucional violences of the Justice System as wich violate human rights of women across the country.